Analisis Yuridis Sengketa Kepemilikan Lahan Situ Ranca Gede Berdasarkan Undang-Undang Pokok Agraria Tahun 1960 - Adinda Santi Kamungnay; Asnawi Asnawi; Faturohman Faturohman (AHKAM, 2025)
The limited number of studies on land ownership disputes in Indonesia forms the background of this research, despite the fact that such conflicts have significant implications for community welfare and environmental sustainability. This study aims to analyze the legal, social, and administrative factors contributing to land ownership conflicts in Situ Ranca Gede and to evaluate the effectiveness of both litigation and non-litigation dispute resolution mechanisms. A qualitative case study approach was employed, involving participants comprising local residents, government officials, and legal experts selected through purposive sampling. Data were collected through in-depth interviews, document analysis, and field observations, and analyzed using thematic and content analysis techniques. The findings reveal that unclear land legal status, overlapping claims between traditional and formal ownership, and low legal awareness among the community are the main drivers of conflict. While litigation provides stronger legal certainty, it is often time-consuming and costly. The study concludes that resolving land disputes requires an integrated approach combining legal enforcement, active community participation, and responsive policy interventions. The implications include theoretical contributions to the strengthening of legal certainty and land governance concepts, as well as practical recommendations for policymakers to improve land registration systems, expand legal education, and develop community-based mediation mechanisms. The research also opens avenues for future studies on the long-term impact of land disputes and interregional comparisons in similar contexts.